Implementasi Penerapan Kebijakan Kawasan Tanpa Rokok (KTR) di Organisasi Perangkat Daerah Kabupaten Merangin - Amelia Gustina Putri; Ridwan Ridwan; Rifqy Azhari (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
The No Smoking Area (KTR) is a form of protection for the community from the adverse effects of smoking, which is regulated in Regional Regulation Number 2 of 2016. This study aims to analyse the implementation of the KTR policy in the Regional Apparatus Organisation (OPD) of Merangin Regency by reviewing four aspects of policy implementation, namely communication, resources, disposition, and bureaucratic structure. This research used a descriptive qualitative approach with data collection techniques in the form of interviews, observation, and documentation. The research informants consisted of OPD parties involved in the implementation of KTR. The results showed that in the communication aspect, KTR policies have been socialised through print and electronic media, but delivery training has not been carried out optimally. In the resource aspect, limited human resources, funds, and facilities are the main obstacles in implementing KTR. In the disposition aspect, most OPDs show commitment in implementing KTR, but have not been supported by providing incentives or awards. In the aspect of bureaucratic structure, there is no special SOP or organisational structure in each OPD for KTR implementation, so the implementation is still not running optimally. In conclusion, the implementation of the KTR policy in Merangin Regency has not run optimally because there are still weaknesses in the four aspects, especially related to coordination, human resources, and supporting institutions.